(untitled) (Bangladesh Rice Journal, 2026)
Rice (Oryza sativa L.) is highly vulnerable to abiotic stresses, particularly in climate-sensitive countries such as Bangladesh, where salinity, submergence, and cold pose major threats to sustainable production. To identify genetic resources for climate-resilient breeding, a multi-trait diversity panel of 464 rice genotypes (CRCIL-464), comprising advanced breeding lines, released varieties, and diverse germplasm, was evaluated for tolerance to these stresses. Salinity screening at the seedling stage using hydroponics identified 32 tolerant and 25 moderately tolerant genotypes based on SES scores, with selected lines further evaluated under soil-based reproductive-stage salinity. Three genotypes (BR11715-4R-13, BR11921-4R-100, and BR12567-5R-91) outperformed the tolerant check IR58443 in grain yield, though yield reductions highlighted differential tolerance mechanisms between stages. Submergence screening revealed wide variability in recovery and survivability, with one genotype (IR14T156) showing complete survival (100%), although most entries were highly sensitive. Cold stress assessment at the seedling stage identified 12 genotypes with partial recovery, and two lines (SVIN 297 and IRRI154-Hd9+Pi9) displayed the highest survivability (83.3%). Collectively, the CRCIL-464 panel demonstrated substantial genetic variation across multiple stresses. The identified tolerant lines represent promising candidates for incorporation into BRRI’s breeding program to develop multi-stress-tolerant rice varieties, thereby enhancing resilience and securing rice production under climate change. Bangladesh Rice J.28(1): 1-16, 2024